Pharmacokinetics Studies of Lurasidone Hydrochloride in Nano Structured Lipid Carrier Formulation for Nasal to Brain Delivery - Kadam, Tanvi; Agrawal, Surendra; Shetty, Saritha (Indian Journal of Pharmaceutical Education and Research)
Aim: Lurasidone Hydrochloride (LH) is a benzothiazole derivative used as an antipsychotic drug for the treatment of schizophrenia. Oral administration of Lurasidone hydrochloride, however, results in low bioavailability and inadequate concentration of Lurasidone in the brain tissue. Therefore, to improve the bioavailability and to achieve desired drug concentration at the site of action, intra nasal administration could be a feasible, non-invasive route for targeting the brain. The current study involves development and validation of reverse phase HPLC method for quantitation of Lurasidone from biological matrix and application of the validated HPLC method to compare pharmacokinetic parameters after intranasal administration of the Nano structured Lipid Carrier (NLC) formulation of Lurasidone in a rat model. Materials and Methods: Lurasidone hydrochloride were obtained from Micro Laboratories (Batch no: LUR4O15005). A reverse phase HPLC method was developed on a binary Gradient HPLC System from Agilent Tech. (1100) for detecting and quantifying Lurasidone from rat plasma. UV (DAD) G13148 detector and Quaternary Gradient (G130A) S.NO. DE9180834) pump along with Fortis C18 column (Particle size: 5 M and dimensions of 4.6 mM×250 mM) was used for chromatographic separation. The chromatographic data was evaluated using the CHEMSTATION 10.1 software. All chemicals used were of analytical grade. The developed method was validated for parameters like linearity, specificity, precision, accuracy, robustness etc., The validated RP-HPLC method was then applied to quantitate LH from plasma of experimental rats. The rats were administered with 0.81 mg/kg per body weight of API of LH and NLC formulation of LH by intra nasal route. Nine blood samples were collected from the retroorbital plexus at 0.00 hr (pre-dose) till 24 hr post dose. After 24 hr, the brain tissue from the treated rats was excised under anesthesia. LH was quantified from the blood plasma and the brain tissue homogenate using the validated RP-HPLC method. Results: The results of the method validation experiments indicate that the developed method is specific, accurate and precise. The response of the HPLC system is linear in the range of LH concentration from 10 μg/mL to 50 μg/mL. The LOD and LOQ of the method are 0.527 μg/mL and 1.598 μg/mL respectively. The method is robust with adequate tolerance to changes in analyst, system and mobile phase composition and mobile phase flow rate. After intranasal administration of LH at a dose equivalent to free LH of 0.81 mg/kg, in NLC formulation, the concentration of LH in the brain tissue was 111.465 μ/g while after administration of free form of LH, the concentration was found to be 27.49 μ/g. This indicates better penetration of the Lurasidone across the Blood Brain Barrier (BBB) due to the nano sized drug carrier vehicles in the NLC formulation. Conclusion: In the current study, the validated reverse phase HPLC method developed to detect and quantify LH, has good precision and accuracy. The method can be successfully applied to quantify LH from API, NLC formulations and biological matrix. The NLC formulation developed is novel and it effectively delivers LH across the BBB. The NLC formulation is thus a possible alternative to oral administration of LH which provides advantages of convenience of administration, increased patient compliance, faster onset of action, lower dosage, better safety and lesser systemic exposure.
Keywords: Nano Lipid Complex; Lurasidone Hydrochloride; Pharmacokinetics; Bio-distribution; RP-HPLC.